Assembling the sense of home in emigrant elite athletes: Cultural transitions, narrative and materiality. (July 2021) - Prato, Luana; Torregrossa, Miquel; Ramis, Yago; Alcaraz, Saul; Smith, Brett
Abstract: Objective: Despite a growing body of literature on cultural transitions, little is known regarding how emigrant elite athletes experience and intra-act with the non-human environment in the host country, and how this affects their sense of home. This study explores the relationships between the material world and the embodied narratives, both personal and socio-cultural, regarding the process of assembling a new sense of home. Design and Methods: Seven Colombian emigrant elite athletes (4 female and 3 male), that emigrated pursuing the Olympic Dream, participated in this study. The philosophical concept of assemblage, from New Materialism approach, was used as a companion and extension of narrative dialogical analysis to analyse life-story interviews. Results: Emigrant athletes define home as a place of refuge where they can express emotions, behave, and communicate in ways that 'feel natural'. During cultural transitions, these athletes assembled a sense of home in two environments: the housing and the sport facilities. The relationships with (a) architectural spaces, (b) objects, (c) food, (d) technological apparels and (d) sport materiality facilitated or hindered the process of assembling a new sense of home in the host country. Conclusions: The transformation of housing and the sport facilities into Home is a crucial process to improve the quality of emigrant athlete's cultural transition. A deeper appreciation of materiality in research and applied practice is needed. Highlights: Emigrant athletes need to feel 'at home' to perform and to adapt to the new country. Home is an assemblage of human and non-human heterogeneous elements. The new sense of home is assembled both in houses and sport facilities. Materiality needs appreciation as it facilitates or hinders assembling a new sense of home.